Barries to the use of contraception among married female youths in rural area of Bardiya district. - Das, Chuman Lal (2008)
SUMMARY: Nepal has high population growth rate (2.24%) and high fertility rate (3.1). Unmet need for family planning among youths (15-24 years) is the highest in Nepal. Nearly 35 percent of 15-24 years of married female has unmet need for family planning. Only 23.2 percent of the youths are currently using family planning services. Only 40 percent of the total need of family planning has been satisfied. So, there is low contraception use, high unmet need and less unmet need satisfied in youths. To explore the barriers for non use of contraception among those youths who either don't want children or want to delay their next birth, this study was designed. This was a descriptive cross-sectional study done in married female youths (15-24 years) of rural areas of Bardiya district. Both quantitative and qualitative research ,methods were used. Three Village Development Committees, one from each electoral constituency, were selected randomly. Nine wards, one in each Village Development Committee, were selected by simple random sampling. A total of 339 married female youths from all wards were further selected purposively. Information was gathered by conducting interviews and Focus Group Discussion with the married female youths. Data analysis was done with the use of logistic regression using SPSS program version 13.0. It was found that Contraceptive Prevalence Rate among the married female youths was 37.7 percent which constituted 25.3 percent spacing and 12.3 percent limiting. Unmet need was 32.6 percent which constituted 22.8 percent spacing and 9.8 percent limiting. Both bivariate and multivariate analysis, with the use of logistic regression, was done to see the association between various factors and unmet need at 95% confidence interval. The study showed that the three selected variables of women's status namely education, occupation and spousal discussion about family planning were strongly associated with unmet need (p-value <.05). Mother with no education, farmer or labour and not discussing with spouses about family planning had higher prevalence of unmet need. Similarly, mother with one child had the higher chances of having unmet need for family planning. The important determining factors or barriers to the use of contraception revealed by the study are : knowledge of family planning, fear of side effects, poor interspousal discussion about the family planning, husband's disapproval on contraception use and influence of mother-in-law's decision making for the use of contraception. Based on the findings, suggested recommendations are : good counseling and education before and during the service provision, specific group interactive program especially for husband and wife of young age and information, education and communication outreach campaign of the family planning programmes targeting mother-in-law in addition to spouses in its efforts to enhance contraceptive use.